Method for preparing lithium nickel manganese oxide positive electrode material through liquid phase deposition

The nickel source was deposited on spherical manganese tetraoxide by liquid deposition method, and the nickel lithium manganate positive electrode material was prepared, which solved the problem of insufficient energy density and working life of the positive electrode material of existing lithium-ion batteries, and achieved high-rate performance and Long-term stable cycle performance.

CN119461513APending Publication Date: 2025-02-18SINOSTEEL ANHUI TIANYUAN TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411605006.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing lithium-ion battery cathode materials have shortcomings in terms of energy density and working life, and the cobalt content in ternary lithium materials is costly, making it difficult to widely use.

Method used

The nickel source is deposited on spherical manganese tetraoxide by liquid deposition method, and a nickel-manganese binary precursor is prepared by evaporating liquid deposition method, and then added to the lithium source and heat treatment is performed to prepare a nickel-manganese lithium positive electrode material.

Benefits of technology

This method makes the nickel-manganese precursor have regular morphology and size characteristics, improves the spherical shape and tap density of the lithium nickel-manganate positive electrode material, increases the contact area between the electrode and the electrolyte, and shortens the lithium ion transmission path. This improves the battery's rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461513A_ABST
    Figure CN119461513A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a lithium nickel manganese oxide positive electrode material through liquid phase deposition, relates to the technical field of lithium ion batteries, and aims to solve the problem that a preparation method of high-voltage spinel lithium nickel manganese oxide needs to be improved. The preparation method comprises the following steps: taking spherical manganous-manganic oxide as a nucleation template, mixing a nickel source with the spherical manganous-manganic oxide in a solution form, adding a surfactant, and uniformly dispersing the obtained mixed solution; loading a nickel source on the template by using an evaporation liquid phase deposition method to prepare a nickel-manganese binary precursor, adding a lithium source, mixing lithium, and carrying out heat treatment to obtain a lithium nickel manganese oxide positive electrode material; the method is simple in step, easy to operate, relatively low in cost and high in product purity, the lithium nickel manganese oxide positive electrode material obtained by the method has good sphericity degree and relatively high tap density, the contact area between an electrode and an electrolyte can be effectively increased, and a lithium ion transmission path is shortened, so that the rate capability of a battery is improved, and the service life of the battery is prolonged. And the prepared lithium nickel manganese oxide positive electrode material is controllable in morphology and size and high in material homogenization degree.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, in particular to a method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition. Background Art

[0002] In order to cope with the potential fossil energy crisis and strengthen the protection of the ecological environment system, people have been looking for new energy storage systems that can replace traditional fossil energy. Among them, lithium-ion batteries stand out with their high theoretical open circuit voltage and energy density, as well as long cycle life, and become a promising new energy storage solution. However, existing lithium-ion batteries urgently need to improve their energy density and working life.

[0003] The cathode material has a significant impact on the performance of lithium-ion batteries. The existing common cathode materials include ternary lithium materials, layered lithium-rich manganese-based materials and olivine-type lithium iron phosphate materials. The lithium-rich materials have the highest reversible specific capacity (>250mAh g -1 ), but due to the structural instability of layered materials in the charged state or at high temperatures, there are serious safety problems in the actual application of batteries; the strong covalent bonds of lithium iron phosphate stabilize oxygen in the crystal structure, making it have good stability, but the electrode material has low energy density and poor ionic conductivity, which limits its further development; ternary lithium materials have always attracted market attention because they have higher battery energy density, better cycle performance and are resistant to low temperatures. For example, the announcement number is CN110600698B, and the name is an invention patent for a secondary structure lithium manganese oxide positive electrode material with high sphericity and its preparation method, which discloses that a manganese source precursor, a lithium source compound, a doping element compound and an additive are mixed, and then pre-burned, dehydrated and crushed to obtain a semi-finished product; the semi-finished product and a cobalt source are mixed and sintered, and then crushed after leaving the kiln to obtain Li (1+x) Mn2 a O b , the recorded R must contain cobalt; however, due to the high cost of the cobalt element contained in the ternary lithium material, it is difficult to be more widely used.

[0004] Therefore, researchers began to focus on a cobalt-free cathode material with great advantages: high-voltage spinel lithium nickel manganese oxide (LiNi 0.5 Mn 1.5O4). This material has a high theoretical specific capacity of 146.7mAh / g and a high discharge platform of 4.7V. In theory, its energy density exceeds 600Wh / Kg, and it is low-cost and environmentally friendly. The preparation methods of high-voltage spinel nickel manganese oxide include solid-phase method and liquid-phase method. The solid-phase method includes ball milling mixing method, etc., and the liquid-phase method includes coprecipitation method, sol-gel method and molten salt method, etc. The solid-phase ball milling method has simple operation process and low cost, but it is difficult to achieve uniform mixing of nickel manganese precursors and control uniform particle size by traditional methods; the liquid-phase method has a complex preparation process, relatively high industrial application cost, and easy to introduce impurities. Therefore, a method for preparing lithium nickel manganese oxide positive electrode material by liquid phase deposition is urgently needed to solve this problem. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition, so as to solve the problem that the preparation method of high-voltage spinel lithium nickel manganese oxide needs to be improved.

[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition, comprising the following specific contents: using spherical manganese tetraoxide as a nucleation template, mixing a nickel source with it in the form of a solution, and adding a surfactant, so that the obtained mixed solution is evenly dispersed; using an evaporative liquid phase deposition method to load the nickel source on the template to obtain a nickel-manganese binary precursor, adding a lithium source to mix the lithium and then heat treating to obtain a lithium nickel manganese oxide positive electrode material.

[0007] Preferably, the particle size of the spherical manganese tetraoxide is 1500-3000 nm, and the surface is a rough spherical surface.

[0008] Preferably, the concentration of nickel ions in the mixed solution is 0.05 mol / L to 0.2 mol / L, the ratio of nickel element to manganese element is 1:3, and the concentration of the surfactant is 0.5 to 1 g / L.

[0009] Preferably, after the mixed solution is dispersed by ultrasound until it is fully mixed, the mixed solution is placed in an evaporation reactor and continuously stirred and dispersed, the stirring speed is 200-250 rpm, the temperature in the evaporation reactor is 140-180° C., and the liquid phase is evaporated to make the nickel salt precipitate and evenly deposit on the surface of the spherical manganese oxide to obtain a dry powder.

[0010] Preferably, the mixed lithium is evenly ground using a planetary ball mill, the ball mill speed is 400-600 rpm, and the ball milling time is 8 hours.

[0011] Preferably, the molar ratio of lithium atoms to nickel atoms added to the nickel-manganese binary precursor is 2.1:1.

[0012] Preferably, the heat treatment is high-temperature sintering in an air atmosphere, the heat treatment temperature is 800-900° C., and the treatment time is 10-15 hours. During the heat treatment, the metal salt is converted into its oxide form, and the heteroatoms are removed in the form of gas.

[0013] Preferably, the nickel source is one or more of nickel acetate, nickel nitrate, and nickel citrate.

[0014] Preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium sulfate.

[0015] Preferably, the surfactant is polyethylene glycol.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The method for preparing lithium nickel manganese oxide positive electrode material by liquid phase deposition, deposits a nickel source on manganese tetraoxide with a specific morphology and controlled particle size. The manganese tetraoxide not only serves as a manganese source, but also serves as a nucleation template for the precipitation of the nickel source. After the liquid phase is evaporated to dryness, a spherical nickel-manganese mixed precursor can be obtained, which makes the obtained nickel-manganese precursor have more regular morphology and size characteristics. Subsequently, it is mixed with lithium and heat-treated to obtain the product lithium nickel manganese oxide. The lithium nickel manganese oxide positive electrode material obtained by this method has good sphericity and high tap density, can effectively increase the contact area between the electrode and the electrolyte, shorten the lithium ion transmission path, thereby improving the battery rate performance, and the prepared lithium nickel manganese oxide positive electrode material has controllable morphology and size, and the material has a high degree of homogeneity.

[0018] 2. The method for preparing lithium nickel manganese oxide positive electrode material by liquid phase deposition has simple steps and is easy to operate, has low cost, high single-pot production capacity, does not introduce heteroatoms, has high product purity, and has a simple process and is easy to scale up industrially, having many advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a microscopic morphology image of the lithium nickel manganese oxide product prepared in Example 1 of the present invention, taken using a transmission electron microscope (SEM).

[0020] Figure 2 This is a spectrum obtained by using X-ray diffraction spectroscopy (XRD) testing of the lithium nickel manganese oxide product prepared in Example 1 of the present invention.

[0021] Figure 3 1C charge and discharge curve of the lithium nickel manganese oxide sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] A method for preparing a lithium nickel manganate positive electrode material by liquid phase deposition includes the following specific contents: using spherical manganese tetraoxide as a nucleation template, mixing a nickel source with it in the form of a solution, and adding a surfactant (such as polyethylene glycol) to obtain a uniformly dispersed mixed solution, wherein the nickel source can be one or more of nickel acetate, nickel nitrate, nickel citrate, etc.; using an evaporative liquid phase deposition method to load the nickel source on the template to obtain a nickel-manganese binary precursor, adding a lithium source to mix the lithium and then heat treating to obtain a lithium nickel manganate positive electrode material, wherein the lithium source can be one or more of lithium carbonate, lithium hydroxide, and lithium sulfate. In addition, for reference, the molar ratio of lithium atoms to nickel atoms added to the nickel-manganese binary precursor is preferably 2.1:1.

[0023] The particle size of the spherical trimanganese tetraoxide is more preferably 1500 to 3000 nm, and the surface is a rough spherical surface.

[0024] In a preferred embodiment, the concentration of nickel ions in the mixed solution is 0.05 mol / L to 0.2 mol / L, the ratio of nickel element to manganese element is 1:3, and the concentration of the surfactant is 0.5 to 1 g / L.

[0025] In the above method for reference, the mixed solution can be further dispersed by ultrasonic dispersion. After being dispersed until fully mixed, the mixed solution is placed in an evaporation reactor and continuously stirred and dispersed. The stirring speed is 200-250 rpm, and the temperature in the evaporation reactor is 140-180°C. The liquid phase is evaporated to make the nickel salt precipitate and evenly deposit on the surface of the spherical manganese oxide to obtain a dry powder.

[0026] The mixed lithium can be evenly ground using a planetary ball mill with a ball mill speed of 400-600 rpm and a ball milling time of 8 hours.

[0027] In the method of the present invention, the heat treatment is preferably high-temperature sintering in an air atmosphere, the purpose of which is to convert the metal salt into its oxide form during the heat treatment process, while removing the heteroatoms in the form of gas; for reference, the heat treatment temperature can be selected to be 800-900°C, and the treatment time can be 10-15h.

[0028] Embodiment 1:

[0029] Take 0.050 mol of nickel acetate and completely dissolve it in 500 g of water, take 0.050 mol of spherical nano manganese tetroxide powder, disperse the powder in the prepared nickel sulfate solution, add 0.45 g of polyethylene glycol to the mixed solution, fully ultrasonically disperse it evenly, then keep it dispersed, heat the mixed solution at 150° C. and evaporate it to dryness to obtain a powder, mix the above powder with 0.053 mol of lithium carbonate by ball milling to obtain a mixed phase precursor, place it in a tubular furnace in an air atmosphere, heat it to 880° C. at a rate of 5° C. per minute, keep it for 10 hours, and take it out after cooling to room temperature, which is recorded as Example 1.

[0030] Embodiment 2:

[0031] Take 0.053 mol of nickel acetate and completely dissolve it in 750 g of water, take 0.053 mol of spherical nano manganese tetroxide powder, disperse the powder in the prepared nickel sulfate solution, add 0.63 g of polyethylene glycol to the mixed solution, fully ultrasonically disperse it evenly, then keep it dispersed, heat the mixed solution at 175°C and evaporate it to dryness to obtain a powder, mix the above powder with 0.056 mol of lithium sulfate by ball milling to obtain a mixed phase precursor, place it in a tubular furnace in an air atmosphere, heat it to 810°C at a rate of 5°C per minute, keep it for 12 hours, and take it out after cooling to room temperature, which is recorded as Example 2.

[0032] Embodiment 3:

[0033] Take 0.183 mol of nickel nitrate and completely dissolve it in 1000 g of water, take 0.183 mol of spherical nano manganese tetraoxide powder, disperse the powder in the prepared nickel sulfate solution, add 0.56 g of polyethylene glycol to the mixed solution, fully ultrasonically disperse it evenly, then keep it dispersed, heat the mixed solution at 140°C and evaporate it to dryness to obtain a powder, mix the above powder with 0.384 mol of lithium hydroxide by ball milling to obtain a mixed phase precursor, place it in a tubular furnace in an air atmosphere, heat it to 830°C at a rate of 5°C per minute, keep it for 12 hours, and take it out after cooling to room temperature, which is recorded as Example 3.

[0034] Embodiment 4:

[0035] 0.035 mol of nickel nitrate and 0.051 mol of nickel acetate were completely dissolved in 800 g of water, 0.086 mol of spherical nano manganese tetraoxide powder was taken, and 0.70 g of polyethylene glycol was added to the mixed solution, the powder was dispersed in the prepared nickel sulfate solution, fully ultrasonically dispersed, and then the dispersion was maintained, the mixed solution was heated at 160° C. and evaporated to dryness to obtain a powder, the above powder was ball-milled and mixed with 0.091 mol of lithium carbonate to obtain a mixed phase precursor, which was placed in a tubular furnace in an air atmosphere, heated to 900° C. at a rate of 5° C. per minute, maintained for 14 h, and taken out after cooling to room temperature, which was recorded as Example 4.

[0036] The test results of the lithium nickel manganese oxide products obtained in the four embodiments are shown in Table 1 below;

[0037] Table 1: Performance test results of lithium nickel manganese oxide products obtained in Examples 1 to 4

[0038]

[0039] Test results:

[0040] 1) Electron microscopy results

[0041] like Figure 1 As shown, the microscopic morphology of lithium nickel manganese oxide prepared in Example 1 is shown. From the SEM shooting results, it can be seen that the lithium nickel manganese oxide positive electrode material prepared by the liquid phase deposition method has a regular morphology and good sphericity.

[0042] 2) X-ray diffraction results

[0043] like Figure 2 As shown, the results of X-ray diffraction confirmed that the synthesized product was lithium nickel manganese oxide, and its crystal structure was spinel configuration.

[0044] 3) Tap density test results

[0045] The tap density test results of the embodiments are shown in Table 1, and the results are all higher than 2g / cm 3 .

[0046] 4) Electrochemical performance test

[0047] The present invention also tests the electrochemical performance of a lithium ion battery prepared using the lithium nickel manganese oxide sample of the embodiment. The specific preparation method is to completely disperse lithium nickel manganese oxide, Super P, and PVDF in NMP in a ratio of 8:1:1, apply the dispersion on a conductive aluminum foil, and assemble it into a button battery. The test voltage range used in the discharge capacity test is 3.5-4.95V. Figure 3 The curve of the sample of Example 1 of the present invention in the 1C charge and discharge capacity test is shown. In the rate performance test, the battery was tested at 1C, 3C and 5C charge and discharge rates (where 1C is equal to 147mAh / g). In the cycle performance test, the battery was cycled 500 times at a 5C rate.

[0048] All these tests are charged and discharged by constant current and constant voltage steps, and the corresponding results are given according to Table 1. According to Table 1, in the embodiment, the 1C discharge capacity range is 130.08-134.72mAh / g; the capacity obtained when fully charged for the first time is 128.26-123.49mAh / g at 2C, 114.39-115.89mAh / g at 3C, and 103.22-106.18mAh / g at 5C, and the 5C 500-cycle capacity retention rate test result is 88.75-90.13, all reaching a high level. Therefore, the samples prepared in the embodiments of the present invention have more excellent capacity, high rate performance and long-term stable cycle performance in lithium-ion batteries.

[0049] The present invention proposes a method for preparing a positive electrode material of lithium nickel manganese oxide by liquid phase deposition, wherein a nickel source is deposited on manganese tetraoxide with a specific morphology and controlled particle size, so that the obtained nickel manganese precursor has a more regular morphology and size characteristics and a higher tap density. In addition to the simple steps and easy operation, the present invention can effectively increase the contact area between the electrode and the electrolyte, shorten the lithium ion transmission path, and thus improve the battery rate performance; on the other hand, the prepared positive electrode material of lithium nickel manganese oxide has controllable morphology and size, a high degree of material homogeneity, no heteroatoms are introduced, the product has high purity, and the process is simple and low in cost, the single-reactor production capacity is high, and it is easy to industrially scale up, which has many advantages.

[0050] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.

[0051] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition, characterized in that: The invention includes the following specific contents: using spherical manganese tetraoxide as a nucleation template, mixing a nickel source with it in the form of a solution, and adding a surfactant, so that the obtained mixed solution is evenly dispersed; using an evaporative liquid phase deposition method to load the nickel source on the template to obtain a nickel-manganese binary precursor, adding a lithium source and mixing lithium, and then heat-treating to obtain a lithium nickel manganese oxide positive electrode material.

2. The method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition according to claim 1, characterized in that: The particle size of the spherical manganese tetraoxide is 1500-3000nm, and the surface is a rough spherical surface.

3. The method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition according to claim 1, characterized in that: The concentration of nickel ions in the mixed solution is 0.05 mol / L to 0.2 mol / L, the ratio of nickel element to manganese element is 1:3, and the concentration of surfactant is 0.5 to 1 g / L.

4. The method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition according to claim 1, characterized in that: After the mixed solution is dispersed by ultrasound until fully mixed, the mixed solution is placed in an evaporation reactor for continuous stirring and dispersion, the stirring speed is 200-250 rpm, the temperature in the evaporation reactor is 140-180° C., and the liquid phase is evaporated to dryness so that the nickel salt is precipitated and evenly deposited on the surface of the spherical manganese oxide to obtain a dry powder.

5. The method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition according to claim 1, characterized in that: The mixed lithium is evenly ground using a planetary ball mill, the speed of the ball mill is 400-600 rpm, and the ball milling time is 8 hours.

6. The method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition according to claim 1, characterized in that: The molar ratio of lithium atoms to nickel atoms added to the nickel-manganese binary precursor is 2.1:

1.

7. The method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition according to claim 1, characterized in that: The heat treatment is high-temperature sintering in an air atmosphere, the heat treatment temperature is 800-900° C., and the treatment time is 10-15 hours. During the heat treatment process, the metal salt is converted into its oxide form, and the heteroatoms are removed in the form of gas.

8. The method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition according to claim 1, characterized in that: The nickel source is one or more of nickel acetate, nickel nitrate and nickel citrate.

9. The method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition according to claim 1, characterized in that: The lithium source is one or more of lithium carbonate, lithium hydroxide and lithium sulfate.

10. The method for preparing a lithium nickel manganese oxide positive electrode material by liquid phase deposition according to claim 1, characterized in that: The surfactant is polyethylene glycol.

Citation Information

Patent Citations

  • Highly spherical secondary structure lithium manganese oxide cathode material and its preparation method

    CN110600698B

  • Preparation method of spherical nickel-lithium manganate anode material

    CN103579607A

  • Preparation method of nickel manganese oxide

    CN113044892A